A vueltas con la ajenidad de los riesgos laborales en el perú: apuntes en tiempos del covid-19 - Cavalié Cabrera, Paul (2026)
We start from the premise that the employee’s risk dependence before the most outstanding circumstances that the employment contract can face during its development, starts from the time this labor bond is established, and it is, in turn, the counterpart of the employee’s lack of involvement on the economic results of the business, owned by the employer, and which his/her work can help to generate. To that extent, we then recognize that the adverse or serious effects that arise throughout the employment relationship, should consider, as much as possible, not to fall on the worker, who is recognized under Labor Law-- since its historical foundation as a legal discipline--as the weakest party in the employment contract.